2018
DOI: 10.1177/1049732318778261
|View full text |Cite
|
Sign up to set email alerts
|

The Imperative for a Triumph-Over-Tragedy Story in Women’s Accounts of Undergoing Chemotherapy for Ovarian Cancer

Abstract: We aimed to examine how women construct their experiences of chemotherapy treatment for ovarian cancer. Through semistructured interviews, we explored the accounts of 18 Australian women about their experiences within a broader cultural imperative-or discourse-to "think positively." By applying a critical realist lens to the analysis, we identified two discursive themes that shaped women's accounts. The "feeling different and managing support" theme highlights the identity challenges women faced because of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Additionally, our finding that the combined intervention helped patients with ovarian cancer through the different chemotherapy cycles supports findings from a previous concept mapping study among a mixed cancer population that revealed that exercise improved coping with the disease and its treatment [32]. Furthermore, this confirms findings from a previous study in patients ovarian cancer showing that patients expected that adopting or maintaining a healthy lifestyle would probably help them during treatment [33]. Other positive experiences due to participating in the PADOVA intervention such as receiving quality supervision, peer support, and well-planned structure likely contributed to high satisfaction scores and are in line with findings from previous studies conducted in patients with other types of cancer [28,34,35].…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, our finding that the combined intervention helped patients with ovarian cancer through the different chemotherapy cycles supports findings from a previous concept mapping study among a mixed cancer population that revealed that exercise improved coping with the disease and its treatment [32]. Furthermore, this confirms findings from a previous study in patients ovarian cancer showing that patients expected that adopting or maintaining a healthy lifestyle would probably help them during treatment [33]. Other positive experiences due to participating in the PADOVA intervention such as receiving quality supervision, peer support, and well-planned structure likely contributed to high satisfaction scores and are in line with findings from previous studies conducted in patients with other types of cancer [28,34,35].…”
Section: Discussionsupporting
confidence: 89%
“…Seeman et al., 2016) and the need for women generally to display strength and stoicism in relation to physical and emotional suffering (e.g. Staneva et al., 2018), we argue that there are meaningful differences around psychological distress stigmas and strength imperatives for African Caribbean women that have important implications for identifying and responding to their emotional wellbeing needs. For example, notions of strength provide African Caribbean women with a cultural link to generations of African-heritage women who have overcome racism and other types of adversity (Edge & Reason, 2005; Nelson et al., 2016).…”
Section: Discussionmentioning
confidence: 87%
“…Although there have been other small qualitative studies that have provided important narratives of the experiences of women living with ovarian cancer [17][18][19][20][21][22][23], to the best of our knowledge, ours is the first interview study to offer both qualitative information and quantitative summaries that assess disease-related and treatment-attributed symptoms and the degree of bother and other impacts of these symptoms on the lives of women with ovarian cancer. The mean time between first diagnosis of ovarian cancer and the qualitative interviews in the current study (4 years and 2 years in Europe and USA, respectively) will have aided the broad collection of patient experiences during the disease and treatment trajectory.…”
Section: Discussionmentioning
confidence: 99%